Simultaneous idiopathic benign paroxysmal positional vertigo and labyrinthitis on different side of ear: A rare occasion of acute vestibulopathy lead to delay in management - Salim, Rosdan; Eh Dam, V Sha Kri (International Journal of Human and Health Sciences (IJHHS), 2022)
Dizziness and acute vertigo are common presenting complaints in the Emergency Department or primary care setting. The etiology can be broadly divided into peripheral and central vestibular disorders and need to be differentiated expeditiously as management is completely different. Diagnosis of unilateral peripheral vestibular disorder (PVD) is usually straight forward based on clinical bed side examination finding. Diagnosis becomes more challenging when a patient presents with bilateral PVD or concomitant pathologies that can lead to delay in diagnosis and management. We report a case of rare simultaneous idiopathic benign paroxysmal positional vertigo (BPPV) and labyrinthitis occurring on different side of the ear. International Journal of Human and Health Sciences Vol. 06 No. 02 April’22 Page: 222-226